Anode-supported solid oxide fuel cells with multilayer LSC/CGO/LSC cathode; Fuel Cells; Vol. 21, iss. 4 - Soloviev A. A. Andrey Aleksandrovich; Kuterbekov K. A. Kayrat Atazhanovich; Nurkenov S. A. Serik Amangeldinovich; Nygymanova A. S. Aysulu Serbolovna; Shipilova A. V. Anna Viktorovna; Smolyanskiy (Smolyansky, Smolyanskii) E. A. Egor Aleksandrovich; Rabotkin S. V. Sergey Viktorovich; Ionov I. V. Igor Vyacheslavovich (2021, 2021)
Title screen